2009
DOI: 10.1136/jnnp.2009.181743
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and the risk of vascular dementia: the Italian Longitudinal Study on Ageing

Abstract: In our population, MetS subjects had an elevated risk of VaD that increased after excluding patients with baseline undernutrition and selecting MetS subjects with high inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 30 publications
3
63
1
2
Order By: Relevance
“…Recent work from Stepp's group clearly demonstrated an increase in stroke infarct severity in OZR (39,40). Given that cognitive impairments and vascular dementia have also been linked to impairments of cerebral blood flow regulation, the cerebrovascular adaptations in MetS may represent key contributors to multiple cerebral pathologies (45,46,48). We previously reported a decrease in cerebral cortical microvascular density associated with MetS and suggested that this rarefaction may contribute to either accumulated stroke risk or poor health outcomes in afflicted individuals (7).…”
Section: Discussionmentioning
confidence: 97%
“…Recent work from Stepp's group clearly demonstrated an increase in stroke infarct severity in OZR (39,40). Given that cognitive impairments and vascular dementia have also been linked to impairments of cerebral blood flow regulation, the cerebrovascular adaptations in MetS may represent key contributors to multiple cerebral pathologies (45,46,48). We previously reported a decrease in cerebral cortical microvascular density associated with MetS and suggested that this rarefaction may contribute to either accumulated stroke risk or poor health outcomes in afflicted individuals (7).…”
Section: Discussionmentioning
confidence: 97%
“…Several population-based studies suggested that the presence of MetS increased the risk of developing age-related CD, mild cognitive impairment (MCI), AD, and vascular dementia (VaD) [8][9][10][11] and the risk of progression from MCI to dementia [11]. Furthermore, individual components of MetS have been linked to the risk of developing CD and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the above conditions have a prolonged occurrence during aging (Seshadri and Wolf 2007;Debette et al 2011;DeCarli 2013;DeCarli et al 1995;Jack et al 2013;Swan et al 1998). A synergistic interaction between the above comorbid conditions and the ongoing dysfunction of BFB and LC may exert several deleterious impacts and enhance cognitive decline and promote MCI and AD (Sloane et al 1999;Benveniste et al 2001;Nakanishi 2003;Dik et al 2007;Solfrizzi et al 2010Solfrizzi et al , 2011Misiak et al 2012;Birdsill et al 2013).…”
Section: Commentsmentioning
confidence: 99%